Terrorism in The Perspective of Islamic Law (Reinterpretation of The ISIS Group's Views Regarding The Concept of Jihad, Takfir, and The Caliphate) - Baihaqi, Yusuf (al-'adalah, 2019)
Differences betweenhumans is natural. The Qur’an also suggests that these differences will continue in linewith the existence of humans on this earth. There are many factors behind the birth ofdifferences between humans, such as religious factors, political factors, ethnic factors, andothers. This paper examines the phenomenon of ISIS (Islamic State of Iraq and Syria)which is a splinter group of Muslims who often launch acts of terror in the name ofIslamic teachings. The emergence of ISIS ultimately gave a bad effect to the face of Islamin the international world because Islam, which is truly a religion of love, was viewedby outsiders as a religion that supported radicalism-terrorism. This study found that theemergence of the ISIS phenomenon was due to misunderstanding in interpreting theverses of the Qur’an about the concepts of jihâd, takfîr and caliphate.